2007
DOI: 10.1111/j.1439-0531.2006.00703.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Fertilizing Potential of Frozen‐thawed dog Spermatozoa Diluted in ACP‐106®using anIn VitroSperm–Oocyte Interaction Assay

Abstract: The aim of present study was to evaluate frozen canine semen with ACP-106 (Powder Coconut Water) using an in vitro sperm--oocyte interaction assay (SOIA). Ten ejaculates from five stud dogs were diluted in ACP-106 containing 20% egg yolk, submitted to cooling in a thermal box for 40 min and in a refrigerator for 30 min. After this period, a second dilution was performed using ACP-106 containing 20% egg yolk and 12% glycerol. Samples were thawed at 38 degrees C for 1 min. Post-thaw motility was evaluated by lig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
2
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 32 publications
0
7
2
2
Order By: Relevance
“…The better results obtained with the current study compared with a previous study using the same extender (Cardoso et al. ) are perhaps because of the reduction in egg yolk concentration from 20% to 10%, thus favouring smaller amounts of lumps and better dissolution, with a consequently improved visualization of sperm cells. The choice to use 10% egg yolk in the present study was based on additional results obtained by our research team (Barbosa et al.…”
Section: Discussioncontrasting
confidence: 45%
See 3 more Smart Citations
“…The better results obtained with the current study compared with a previous study using the same extender (Cardoso et al. ) are perhaps because of the reduction in egg yolk concentration from 20% to 10%, thus favouring smaller amounts of lumps and better dissolution, with a consequently improved visualization of sperm cells. The choice to use 10% egg yolk in the present study was based on additional results obtained by our research team (Barbosa et al.…”
Section: Discussioncontrasting
confidence: 45%
“…The better results obtained with the current study compared with a previous study using the same extender (Cardoso et al 2007) are perhaps because of the reduction in egg yolk concentration from 20% to 10%, thus favouring smaller amounts of lumps and better dissolution, with a consequently improved visualization of sperm cells. The choice to use 10% egg yolk in the present study was based on additional results obtained by our research team (Barbosa et al 2009) using ACP-106c, which showed that this lower concentration is more practical for the analysis of sperm motility (objective or computerized) because of the lower viscosity of the medium, which facilitates sperm cell displacement.…”
Section: Discussioncontrasting
confidence: 39%
See 2 more Smart Citations
“…Freezing techniques and the evaluation of fertilizing potential of frozen-thawed dog spermatozoa have been intensively investigated in several studies (Zavos et al, 1992;Martins-Bessa et al, 2006;Schafer-Somi et al, 2006Cardoso et al, 2007). However, determining the viability of sperm of dogs of different ages has not been the subject of focus.…”
Section: Discussionmentioning
confidence: 99%